Professional Self-Identification of Future Educators as a Form of Personal Growth - Potapchuk, Tetiana; Makaruk, Olha; Kravets, Nadia; Annenkovа, Nataliia (Journal of History Culture and Art Research, 2020)
The article covers the issue of professional self-identification of future specialists. The meaning of the concept of “self-identification” has been revealed, the circle of related concepts highlighted, and the process of self-identification in the context of personal self-determination analyzed. The purpose and objectives of the study have led to the need for a comprehensive use of the basic general scientific methods which are interchangeable at different stages of study. Among them, we should point out theoretical methods (scientific analysis, comparison, systematization, classification, integration of information obtained from psychological, pedagogical literature to design the scholarly apparatus of the study) and empirical research methods (diagnostic techniques: observation, surveying, testing). Professional self-identification is a very important component in the path of professional development of a would-be specialist, as a future teacher must not only have theoretical knowledge and empirical skills, he must also clearly understand the purpose, objects, means, possible difficulties, prospects of his activity, etc. Based on the psychological and pedagogical analysis of scholarly ideas, the meaning and content of definitions, concepts, and conceptual provisions revealing the specific features of the future educators' professional self-identification have been established. It has been proved that a teacher is one of the most responsible professions; helping people, he must be able to maintain aloofness as well as provide professional assistance, and for this, he requires a high level of professional training. It has been determined that the concept of “professional self-identification” correlates with such currently popular notions as self-determination, self-actualization, self-fulfillment, and self-awareness. The study materials may be applied when preparing the lectures on pedagogical subjects such as Pedagogy, History of Pedagogy, Educational and Developmental Psychology, Methodology of Pedagogical Work.